A high-strength and high-toughness ceramic coating and its use method
By optimizing the formulation and preparation process of ceramic coatings, nano silica sol, modified inorganic fillers and other components are used to solve the problem of insufficient toughness of traditional ceramic coatings, and high-strength and high-toughness ceramic coatings are achieved, which are suitable for occasions where there are high requirements for coating performance.
Patent Information
- Application Number
- CN202510272148.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-04
AI Technical Summary
Traditional ceramic coatings have limited their application in occasions where there are high requirements for coating strength and toughness due to problems such as insufficient toughness and easy cracking.
By optimizing the formulation and preparation process of ceramic coatings, nanosilica sols, modified inorganic fillers, methyldimethoxysilane and polyborosiloxane are used to form a strong and elastic coating.
It achieves high strength and toughness of ceramic coatings, can withstand large external forces and impacts without easy breakage or peeling, extends service life and reduces the frequency of repair and replacement.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic coatings and relates to a high-strength and high-toughness ceramic coating and a use method thereof. Background Art
[0002] In the existing field of coating technology, ceramic coatings are widely used in various industrial fields due to their excellent wear resistance, corrosion resistance, high temperature resistance, etc. However, traditional ceramic coatings often have problems such as insufficient toughness and easy cracking, which limits their application in some occasions with high requirements for coating strength and toughness.
[0003] At present, some improvement methods are mainly focused on the adjustment of coating formula and optimization of preparation process. For example, the strength and toughness of coating are improved by adding various modifiers and enhancers, or the performance of coating is improved by changing the preparation process of coating. Therefore, it is of great practical significance and application value to develop a high-strength and high-toughness ceramic coating with simple preparation process, easy-to-obtain raw materials and stable coating performance.
[0004] Based on the above background technology, the present invention proposes a high-strength and high-toughness ceramic coating and a preparation method thereof, aiming to prepare a ceramic coating with excellent strength and toughness by optimizing the formula and preparation process of the coating to meet the high requirements for coating performance in different fields. Summary of the invention
[0005] The object of the present invention is to provide a high-strength and high-toughness ceramic coating and a method for using the same, which has the characteristics of high strength and high toughness.
[0006] The purpose of the present invention can be achieved by the following technical solutions: A high-strength and high-toughness ceramic coating, comprising a primer and a topcoat, The formula of the primer is as follows: by mass percentage, 20-30% nano-silica sol, 5-10% inorganic pigment, 5-10% modified inorganic filler, 30-40% methyl dimethoxy silane, 10-20% polyborosiloxane, 1-5% formic acid, and 5-10% deionized water; The preparation method of the modified inorganic filler is as follows: S1.1: Sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 20-30%, titanium diboride is dispersed in the sodium silicate solution, wherein the mass ratio of sodium silicate to titanium diboride is (1-2):1, and then 1wt% of a silane coupling agent is added, ultrasonicated for 4-6h to obtain a solid-liquid mixture, filtered and dried to obtain a mixture A; S1.2: Mixing mixture A and ceramic hollow microspheres in a mass ratio of 1:1 to obtain mixture B; S1.3: dissolving borax in deionized water to obtain a borax solution with a mass fraction of 30%, adding mixture B to the borax solution, wherein the mass ratio of mixture B to borax is 1:2, stirring in a stirrer at a speed of 200 r / min to obtain a solid-liquid mixture C; S1.4: Add 3 wt% urea to the solid-liquid mixture C, transfer to a muffle furnace preheated to 300°C, and burn for 1 to 3 minutes. After complete combustion, heat from the preheating temperature to 500 to 600°C, and calcine at 500 to 600°C for 2 hours to obtain a mixture D. After cooling to room temperature, crush and grind to obtain the modified inorganic filler; The formula of the topcoat is as follows: by mass percentage, 20-30% nano-silica sol, 5-10% hollow glass microbeads, 1-5% borax, 30-40% methyldimethoxysilane, 1-5% formic acid, 5-15% polyborosiloxane, and 10-20% deionized water.
[0007] Further, the preparation method of the primer is as follows: S2.1: Put the inorganic pigment and the modified inorganic filler into a ball mill according to the proportion at room temperature and grind them at a speed of 800 r / min for 0.5-1 h to obtain a mixed powder; S2.2: Disperse the mixed powder in nano-silica sol, sonicate for 2-3 hours, and obtain primer component A after dispersion; S2.3: Mix formic acid and deionized water in proportion to obtain a primer C component, mix methyldimethoxysilane and polyborosiloxane in proportion, put into a mixer and stir at a speed of 300 r / min for 20 min to obtain a primer B component; S2.4: Add primer C component to primer B component to obtain primer B+C component, stir primer A component at a speed of 120-140 r / min, add primer B+C component after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth of 500 mesh or more to obtain the primer.
[0008] Further, the preparation method of the topcoat is as follows: S3.1: Put hollow glass microspheres and borax into a ball mill according to proportion at room temperature and grind them at a speed of 600 r / min for 0.5-1 h to obtain a mixed powder; S3.2: Disperse the mixed powder in nano-silica sol in proportion at room temperature, perform ultrasonic treatment for 2-3 hours, and obtain topcoat component A after dispersion; S3.3: Formic acid and deionized water are mixed in proportion to obtain a topcoat component C, methyldimethoxysilane and polyborosiloxane are mixed in proportion, and the mixture is put into a mixer and stirred at a speed of 200 r / min for 10 to 20 min to obtain a topcoat component B; S3.4: Add the topcoat component C to the topcoat component B to obtain the topcoat component B+C, stir the topcoat component A at a speed of 120-140 r / min, add the topcoat component B+C after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth with a mesh size of 300 or more to obtain the topcoat.
[0009] Furthermore, the silane coupling agent in S1.1 is one or more of silane coupling agent KH-550, silane coupling agent KH-560, and silane coupling agent KH-792.
[0010] Furthermore, the particle size of the ceramic hollow microbeads in S1.2 is 3 μm.
[0011] Furthermore, in S1.4, the particle size of the modified inorganic filler is 800 mesh.
[0012] A method for using a high-strength and high-toughness ceramic coating, the method for using the ceramic coating is as follows: S7.1: sandblast the surface of the substrate, and purge the magnesium alloy surface after sandblasting with nitrogen gas at a flow rate of 20 m / s, the purity of the nitrogen gas is 99.99%, and the purge time is 0.5 h; S7.2: First spray the primer on the treated substrate surface, with the spraying parameters of spraying distance 60mm and spraying rate 80mm / s; S7.3: Spray the topcoat directly after spraying the primer. The spraying parameters are spraying distance 40 mm, spraying rate 60 mm / s, and drying at 80℃ for 15 minutes after spraying. S7.4: Polish and grind the surface of the substrate after the topcoat has dried. First, use a grinding head composed of 500 mesh elastic modules to grind for 20 seconds, and then use a grinding head composed of 2000 mesh elastic modules to grind for 10 to 30 seconds. After grinding, bake and cure again to complete the use of the coating.
[0013] Furthermore, the material for sandblasting in S7.1 is brown corundum with a particle size of 200 mesh, the sandblasting distance is 50 mm, the sandblasting angle is 60°, and the sandblasting time is 10 min.
[0014] Furthermore, the pressure applied by the grinding head of the hard grinding block for polishing in S7.4 to the surface of the tile is 1.5 MPa, and the pressure applied by the grinding head composed of the elastic module to the surface of the tile is 0.3~0.5 MPa.
[0015] Furthermore, the parameters for baking and curing in S7.4 are first baking at 100°C for 5-8 min in the low temperature section, heating to 300°C for 5 min, and then heating to 450°C for 15 min.
[0016] The invention enables the primer to form a strong and elastic coating by carefully selecting and proportioning various raw materials, thereby providing excellent substrate support for the ceramic coating.
[0017] As the main inorganic component, nano-silica sol can significantly improve the hardness and wear resistance of the coating. Its nano-scale particle size makes the coating denser and effectively blocks external erosion. At the same time, chemical bonding may occur between silica and other components to enhance the cohesion of the coating. Through a specific modification process, inorganic fillers play a role in strengthening and toughening the coating. The active groups on its surface may react with other components to form a strong chemical bond and improve the overall strength of the coating. At the same time, the addition of fillers can also reduce the thermal expansion coefficient of the coating and improve the thermal shock resistance. As an organic silicon compound, methyldimethoxysilane can cross-link with other components to form a three-dimensional network structure, significantly improving the toughness and elasticity of the coating. At the same time, it can also enhance the adhesion between the coating and the substrate; the addition of polyborosiloxane further enhances the heat resistance and chemical stability of the coating. Its special molecular structure enables the coating to maintain good performance at high temperatures. In addition, polyborosiloxane may react with other ingredients to form a denser coating structure. Formic acid, as a catalyst and regulator, can promote the reaction rate between the ingredients in the coating and make the coating solidify faster. At the same time, it can also adjust the viscosity and fluidity of the coating to ensure construction performance.
[0018] Complex cross-linking reactions occur between inorganic and organic components such as nano-silica sol, methyldimethoxysilane and polyborosiloxane. These reactions not only enhance the inorganic-organic interface bonding inside the coating, but also form a denser and tougher coating structure. At the same time, the addition of modified inorganic fillers further enhances the strength and toughness of the coating, making the entire ceramic coating have more excellent comprehensive properties.
[0019] Nano-silica sol is a colloidal solution. The nano-scale silica particles it contains have a large number of unsaturated bonds and hydroxyl groups in different bonding states on their surfaces. These hydroxyl groups provide active sites for cross-linking reactions. Methyldimethoxysilane is an organosilicon compound. The methoxy groups in its molecules can be hydrolyzed into hydroxyl groups under appropriate conditions, and then undergo condensation reactions with hydroxyl groups or other active groups in the nano-silica sol to form Si-O-Si bonds. The addition of polyborosiloxane further enriches the structure of the cross-linked network. Polyborosiloxane molecules contain siloxane units and boron elements. The introduction of boron elements can form a more complex and stable cross-linked network through the interaction of boron oxygen bonds and silicon oxygen bonds. This cross-linked network not only improves the strength and toughness of the coating, but also gives the coating unique self-healing ability and heat resistance.
[0020] The cross-linking effect of polyborosiloxane makes the molecular structure of the paint primer more compact and stable, thereby improving the strength and toughness of the paint; polyborosiloxane has good heat resistance and can keep the physical and chemical properties of the paint unchanged at high temperatures, thereby improving the thermal stability of the paint; the reversible bonding mechanism in polyborosiloxane enables the paint to repair tiny cracks or defects by itself after being damaged, thereby extending the service life of the paint; the addition of polyborosiloxane can also reduce the viscosity of the paint, improve its processing performance, and make the paint easier to apply and cure.
[0021] The invention prepares a modified inorganic filler. Sodium silicate is used as a solvent to help disperse titanium diboride and form a certain bonding effect. Titanium diboride can significantly improve the hardness, wear resistance and high temperature resistance of the filler, thereby improving the overall performance of the coating. Ceramic hollow microspheres have the characteristics of light weight, high strength, heat insulation and the like. After being added, the density of the coating can be reduced, and the impact resistance and heat insulation performance of the coating can be improved. Borax plays a role of a flux in the combustion and roasting process, and is conducive to the reaction and combination between the components.
[0022] The present invention modifies inorganic substances through ultrasonic treatment of sodium silicate, titanium diboride and silane coupling agent and subsequent steps, thereby enhancing the compatibility and bonding force between the filler and the coating matrix, which helps to improve the overall strength and toughness of the coating; the further introduction of ceramic hollow microspheres not only reduces the density of the coating, but also improves the thermal insulation and wear resistance of the coating, while maintaining good mechanical properties, and then undergoes high-temperature calcination to form a more stable and hard substance, further improving the hardness and durability of the filler. The ceramic hollow microspheres of the present invention are purchased from Shanghai Huijing Sub-Nano New Materials Co., Ltd., and have a particle size of 3μm. These advantages enable the modified inorganic filler to exert excellent performance in high-strength and high-toughness ceramic coatings.
[0023] During the preparation of modified inorganic fillers, one end of the silane coupling agent reacts with the silanol group in sodium silicate and the hydroxyl group on the surface of titanium diboride to form a chemical bond, thereby improving the surface properties of the filler. At high temperatures, the gas and borax produced by the decomposition of urea undergo redox reactions and melt rearrangement with other components. These reactions help to form modified inorganic fillers with high strength and high toughness.
[0024] The topcoat formula of the present invention achieves a good combination of high strength and high toughness by carefully selecting each component and its ratio, and may also have good wear resistance, corrosion resistance and high temperature resistance. Nano silica sol, as the main inorganic component, provides hardness and wear resistance of the coating, and helps to form a dense coating structure; hollow glass microspheres play the role of lightweight filling and enhancing the toughness of the coating, and may improve the thermal insulation performance of the coating; borax can promote the chemical reaction between the components during the baking process, and help to form a stable coating structure; methyldimethoxysilane, as an organic silicon compound, provides flexibility and adhesion of the coating, and forms a dense cross-linked structure with the inorganic components; the addition of polyborosiloxane introduces boron elements and siloxane structures, significantly improving the high temperature resistance and chemical stability of the coating, and enhancing the hardness and wear resistance of the coating.
[0025] Borax is introduced into the topcoat formula of the present invention. At 450°C, the borax will partially decompose to produce boron oxide, which will react chemically with other coating components to promote the curing of the coating. The boron atoms in the boron oxide will replace part of the silicon atoms in the polyborosiloxane molecular chain to form new boron-oxygen bonds (BO) or silicon-boron-oxygen bonds (Si-OB). This substitution reaction helps to enhance the interaction between polymer chains, improve the crosslinking density and stability of the coating, and form a more stable and dense coating structure. In addition, the boron oxide produced by the decomposition of borax itself also has excellent high temperature resistance, and can maintain the stability and integrity of the coating under high temperature environment, thereby improving the high temperature resistance of the coating. The addition of borax can also enhance the hardness of the coating. Through the interaction with other components, the borax helps to form a harder coating structure, improve the wear resistance and scratch resistance of the coating, and the borax promotes the chemical reaction between the coating and the substrate at high temperature, thereby enhancing the adhesion of the coating, which enables the coating to be more firmly attached to the substrate, thereby improving the durability and service life of the coating.
[0026] Sandblasting is used to roughen the surface of the substrate, and nitrogen purging is used to remove surface impurities. This method can significantly improve the bonding strength between the coating and the substrate and ensure the firmness of the coating. By precisely controlling parameters such as spraying distance and spraying rate, the coating can be evenly and delicately adhered to the surface of the substrate, avoiding defects such as uneven coating thickness and bubbles. The segmented baking and curing method is adopted, first baking at a low temperature and then gradually heating to high temperature. This method can ensure that the organic components in the coating are fully volatilized and cured, thereby improving the hardness and wear resistance of the coating. At the same time, the baking and curing process can also eliminate the stress inside the coating and improve the toughness and impact resistance of the coating.
[0027] By optimizing the formula and improving the construction method, the ceramic coating of the present invention has the dual advantages of high strength and high toughness. This coating can withstand large external forces and impacts without being easily broken or peeled off, thereby extending the service life. The ceramic coating of the present invention uses environmentally friendly raw materials and energy-saving construction methods, reducing environmental pollution and energy consumption. At the same time, the high performance of the coating also means that the frequency of maintenance and replacement can be reduced during use, thereby further reducing the cost of use. DETAILED DESCRIPTION
[0028] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0029] Example 1 The formula of the primer is as follows: 20% nano-silica sol, 10% inorganic pigment, 10% modified inorganic filler, 35% methyl dimethoxy silane, 15% polyborosiloxane, 5% formic acid, and 5% deionized water; The preparation method of the modified inorganic filler is as follows: S1.1: Sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 25%, titanium diboride is dispersed in the sodium silicate solution, wherein the mass ratio of sodium silicate to titanium diboride is 2:1, and then 1wt% of silane coupling agent KH-550 is added, and ultrasonic treatment is performed for 4h to obtain a solid-liquid mixture, which is filtered and dried to obtain a mixture A; S1.2: Mixing mixture A and ceramic hollow microspheres with a particle size of 3 μm in a mass ratio of 1:1 to obtain mixture B; S1.3: dissolving borax in deionized water to obtain a borax solution with a mass fraction of 30%, adding mixture B to the borax solution, wherein the mass ratio of mixture B to borax is 1:2, stirring in a stirrer at a speed of 200 r / min to obtain a solid-liquid mixture C; S1.4: Add 3 wt% urea to the solid-liquid mixture C, transfer to a muffle furnace preheated to 300°C, and burn for 2 minutes. After the combustion is complete, heat the mixture from the preheating temperature to 500°C, and calcine at 500°C for 2 hours to obtain a mixture D. After cooling to room temperature, crush and grind to obtain the modified inorganic filler with a particle size of 800 mesh; The preparation method of the primer is as follows: S2.1: Put the inorganic pigment and the modified inorganic filler into a ball mill according to the proportion at room temperature and grind them at a speed of 800 r / min for 1 h to obtain a mixed powder; S2.2: Disperse the mixed powder in nano-silica sol, sonicate for 3 h, and obtain primer component A after dispersion; S2.3: Mix formic acid and deionized water in proportion to obtain a primer C component, mix methyldimethoxysilane and polyborosiloxane in proportion, put into a mixer and stir at a speed of 300 r / min for 20 min to obtain a primer B component; S2.4: Add primer C component to primer B component to obtain primer B+C component, stir primer A component at a speed of 140 r / min, add primer B+C component after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth of 500 mesh or more to obtain the primer.
[0030] The topcoat formula is as follows: 30% nano silica sol, 5% hollow glass microspheres, 5% borax, 35% methyl dimethoxy silane, 5% formic acid, 10% polyborosiloxane, and 10% deionized water; The preparation method of the topcoat is as follows: S3.1: Put hollow glass microspheres and borax into a ball mill according to proportion at room temperature and grind them at a speed of 600 r / min for 1 h to obtain a mixed powder; S3.2: Disperse the mixed powder in nano-silica sol in proportion at room temperature, perform ultrasonic treatment for 3 h, and obtain topcoat component A after dispersion; S3.3: formic acid and deionized water are mixed in proportion to obtain a topcoat component C, methyldimethoxysilane and polyborosiloxane are mixed in proportion, and the mixture is put into a mixer and stirred at a speed of 200 r / min for 20 min to obtain a topcoat component B; S3.4: Add the topcoat component C to the topcoat component B to obtain the topcoat component B+C, stir the topcoat component A at a speed of 140 r / min, add the topcoat component B+C after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth with a mesh size of 300 or more to obtain the topcoat.
[0031] The method of using the ceramic coating is as follows: S7.1: The substrate surface is subjected to sandblasting treatment. The sandblasting material is brown corundum with a particle size of 200 mesh. The sandblasting distance is 50 mm, the sandblasting angle is 60°, and the sandblasting time is 10 min. After the sandblasting treatment, the magnesium alloy surface after the sandblasting treatment is purged with nitrogen gas at a flow rate of 20 m / s. The purity of the nitrogen gas is 99.99%, and the purging time is 0.5 h. S7.2: First spray the primer on the treated substrate surface, with the spraying parameters of spraying distance 60mm and spraying rate 80mm / s; S7.3: Spray the topcoat directly after spraying the primer. The spraying parameters are spraying distance 40 mm, spraying rate 60 mm / s, and drying at 80℃ for 15 minutes after spraying. S7.4: Polish and grind the surface of the substrate after the topcoat has dried. First, use a grinding head composed of 500 mesh elastic modules to grind for 20 seconds at a pressure of 1.5 MPa, and then use a grinding head composed of 2000 mesh elastic modules to grind for 20 seconds at a pressure of 0.4 MPa. After grinding, bake and cure again. First, bake at 100°C for 8 minutes at a low temperature, then heat to 300°C for 5 minutes, and then heat to 450°C for 15 minutes to complete the use of the coating.
[0032] Example 2 The formula of the primer is as follows: 30% nano-silica sol, 5% inorganic pigment, 5% modified inorganic filler, 30% methyl dimethoxy silane, 20% polyborosiloxane, 1% formic acid, and 9% deionized water; The preparation method of the modified inorganic filler is as follows: S1.1: Sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 20%, titanium diboride is dispersed in the sodium silicate solution, wherein the mass ratio of sodium silicate to titanium diboride is 1:1, and then 1wt% of silane coupling agent KH-560 is added, and ultrasonic treatment is performed for 4h to obtain a solid-liquid mixture, which is filtered and dried to obtain a mixture A; S1.2: Mixing mixture A and ceramic hollow microspheres with a particle size of 3 μm in a mass ratio of 1:1 to obtain mixture B; S1.3: dissolving borax in deionized water to obtain a borax solution with a mass fraction of 30%, adding mixture B to the borax solution, wherein the mass ratio of mixture B to borax is 1:2, stirring in a stirrer at a speed of 200 r / min to obtain a solid-liquid mixture C; S1.4: Add 3 wt% urea to the solid-liquid mixture C, transfer to a muffle furnace preheated to 300°C, and burn for 1 min. After complete combustion, heat from the preheating temperature to 500°C, and calcine at 500°C for 2 h to obtain a mixture D. After cooling to room temperature, crush and grind to obtain the modified inorganic filler with a particle size of 800 mesh; The preparation method of the primer is as follows: S2.1: Put the inorganic pigment and the modified inorganic filler into a ball mill according to the proportion at room temperature and grind them at a speed of 800 r / min for 0.5 h to obtain a mixed powder; S2.2: Disperse the mixed powder in nano-silica sol, sonicate for 2 h, and obtain primer component A after dispersion; S2.3: Mix formic acid and deionized water in proportion to obtain a primer C component, mix methyldimethoxysilane and polyborosiloxane in proportion, put into a mixer and stir at a speed of 300 r / min for 20 min to obtain a primer B component; S2.4: Add primer C component to primer B component to obtain primer B+C component, stir primer A component at a speed of 120 r / min, add primer B+C component after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth with a mesh size of 500 or more to obtain the primer.
[0033] The topcoat formula is as follows: 20% nano silica sol, 10% hollow glass microspheres, 5% borax, 40% methyl dimethoxy silane, 5% formic acid, 5% polyborosiloxane, and 15% deionized water; The preparation method of the topcoat is as follows: S3.1: Put hollow glass microspheres and borax into a ball mill according to proportion at room temperature and grind them at a speed of 600 r / min for 0.5 h to obtain a mixed powder; S3.2: Disperse the mixed powder in nano-silica sol in proportion at room temperature, perform ultrasonic treatment for 2 h, and obtain topcoat component A after dispersion; S3.3: formic acid and deionized water are mixed in proportion to obtain a topcoat component C, methyldimethoxysilane and polyborosiloxane are mixed in proportion, and the mixture is put into a mixer and stirred at a speed of 200 r / min for 10 min to obtain a topcoat component B; S3.4: Add the topcoat component C to the topcoat component B to obtain the topcoat component B+C, stir the topcoat component A at a speed of 120 r / min, add the topcoat component B+C after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth with a mesh size of 300 or more to obtain the topcoat.
[0034] The method of using the ceramic coating is as follows: S7.1: The substrate surface is subjected to sandblasting treatment. The sandblasting material is brown corundum with a particle size of 200 mesh. The sandblasting distance is 50 mm, the sandblasting angle is 60°, and the sandblasting time is 10 min. After the sandblasting treatment, the magnesium alloy surface after the sandblasting treatment is purged with nitrogen gas at a flow rate of 20 m / s. The purity of the nitrogen gas is 99.99%, and the purging time is 0.5 h. S7.2: First spray the primer on the treated substrate surface, with the spraying parameters of spraying distance 60mm and spraying rate 80mm / s; S7.3: Spray the topcoat directly after spraying the primer. The spraying parameters are spraying distance 40 mm, spraying rate 60 mm / s, and drying at 80℃ for 15 minutes after spraying. S7.4: Polish and grind the surface of the substrate after the topcoat has dried. First, use a grinding head composed of 500 mesh elastic modules to grind for 20 seconds at a pressure of 1.5 MPa, and then use a grinding head composed of 2000 mesh elastic modules to grind for 10 seconds at a pressure of 0.3 MPa. After grinding, bake and cure again. First, bake at 100°C for 5 minutes at a low temperature, then heat to 300°C for 5 minutes, and then heat to 450°C for 15 minutes to complete the use of the coating.
[0035] Example 3 The formula of the primer is as follows: 20% nano-silica sol, 10% inorganic pigment, 5% modified inorganic filler, 40% methyl dimethoxy silane, 10% polyborosiloxane, 5% formic acid, and 10% deionized water; The preparation method of the modified inorganic filler is as follows: S1.1: Sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 30%, titanium diboride is dispersed in the sodium silicate solution, wherein the mass ratio of sodium silicate to titanium diboride is 2:1, and then 1wt% of silane coupling agent KH-792 is added, and ultrasonic treatment is performed for 6h to obtain a solid-liquid mixture, which is filtered and dried to obtain a mixture A; S1.2: Mixing mixture A and ceramic hollow microspheres with a particle size of 3 μm in a mass ratio of 1:1 to obtain mixture B; S1.3: dissolving borax in deionized water to obtain a borax solution with a mass fraction of 30%, adding mixture B to the borax solution, wherein the mass ratio of mixture B to borax is 1:2, stirring in a stirrer at a speed of 200 r / min to obtain a solid-liquid mixture C; S1.4: Add 3 wt% urea to the solid-liquid mixture C, transfer to a muffle furnace preheated to 300°C, and burn for 3 minutes. After the combustion is complete, heat the mixture from the preheating temperature to 600°C, and calcine at 600°C for 2 hours to obtain a mixture D. After cooling to room temperature, crush and grind to obtain the modified inorganic filler with a particle size of 800 mesh; The preparation method of the primer is as follows: S2.1: Put the inorganic pigment and the modified inorganic filler into a ball mill according to the proportion at room temperature and grind them at a speed of 800 r / min for 1 h to obtain a mixed powder; S2.2: Disperse the mixed powder in nano-silica sol, sonicate for 3 h, and obtain primer component A after dispersion; S2.3: Mix formic acid and deionized water in proportion to obtain a primer C component, mix methyldimethoxysilane and polyborosiloxane in proportion, put into a mixer and stir at a speed of 300 r / min for 20 min to obtain a primer B component; S2.4: Add primer C component to primer B component to obtain primer B+C component, stir primer A component at a speed of 120 r / min, add primer B+C component after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth with a mesh size of 500 or more to obtain the primer.
[0036] The topcoat formula is as follows: 25% nano silica sol, 8% hollow glass microspheres, 1% borax, 30% methyl dimethoxy silane, 1% formic acid, 15% polyborosiloxane, and 20% deionized water; The preparation method of the topcoat is as follows: S3.1: Put hollow glass microspheres and borax into a ball mill according to proportion at room temperature and grind them at a speed of 600 r / min for 1 h to obtain a mixed powder; S3.2: Disperse the mixed powder in nano-silica sol in proportion at room temperature, perform ultrasonic treatment for 3 h, and obtain topcoat component A after dispersion; S3.3: formic acid and deionized water are mixed in proportion to obtain a topcoat component C, methyldimethoxysilane and polyborosiloxane are mixed in proportion, and the mixture is put into a mixer and stirred at a speed of 200 r / min for 20 min to obtain a topcoat component B; S3.4: Add the topcoat component C to the topcoat component B to obtain the topcoat component B+C, stir the topcoat component A at a speed of 140 r / min, add the topcoat component B+C after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth with a mesh size of 300 or more to obtain the topcoat.
[0037] The method of using the ceramic coating is as follows: S7.1: The substrate surface is subjected to sandblasting treatment. The sandblasting material is brown corundum with a particle size of 200 mesh. The sandblasting distance is 50 mm, the sandblasting angle is 60°, and the sandblasting time is 10 min. After the sandblasting treatment, the magnesium alloy surface after the sandblasting treatment is purged with nitrogen gas at a flow rate of 20 m / s. The purity of the nitrogen gas is 99.99%, and the purging time is 0.5 h. S7.2: First spray the primer on the treated substrate surface, with the spraying parameters of spraying distance 60mm and spraying rate 80mm / s; S7.3: Spray the topcoat directly after spraying the primer. The spraying parameters are spraying distance 40 mm, spraying rate 60 mm / s, and drying at 80℃ for 15 minutes after spraying. S7.4: Polish and grind the surface of the substrate after the topcoat has dried. First, use a grinding head composed of 500 mesh elastic modules to grind for 20 seconds at a pressure of 1.5 MPa, and then use a grinding head composed of 2000 mesh elastic modules to grind for 30 seconds at a pressure of 0.5 MPa. After grinding, bake and cure again. First, bake at 100°C for 8 minutes at a low temperature, then heat to 300°C for 5 minutes, and then heat to 450°C for 15 minutes to complete the use of the coating.
[0038] Comparative Example 1 In this comparative example, polyborosiloxane is not added to the primer formulation, and the remaining steps are consistent with those of Example 1.
[0039] Comparative Example 2 In this comparative example, no sodium silicate is added during the preparation of the modified inorganic filler in the primer formulation, and the remaining steps are consistent with those in Example 1.
[0040] Comparative Example 3 In this comparative example, titanium diboride is not added during the preparation of the modified inorganic filler in the primer formulation, and the remaining steps are consistent with those of Example 1.
[0041] Comparative Example 4 In this comparative example, no ceramic hollow microspheres were added during the preparation of the modified inorganic filler in the primer formulation, and the remaining steps were consistent with those in Example 1.
[0042] Comparative Example 5 In this comparative example, no borax was added during the preparation of the modified inorganic filler in the primer formulation, and the remaining steps were consistent with those in Example 1.
[0043] Comparative Example 6 In this comparative example, borax is not added to the topcoat formula, and the remaining steps are consistent with those of Example 1.
[0044] Comparative Example 7 In this comparative example, polyborosiloxane is not added to the topcoat formula, and the remaining steps are consistent with Example 1.
[0045] The performance of the samples coated with ceramic coating obtained in the examples and comparative examples was tested, and the test methods are summarized in the following table:
[0046] The test results are summarized in the following table:
[0047] Experiments show that the ceramic coating prepared by the present invention has high strength and toughness. The addition of polyborosiloxane to the primer and the modification of the inorganic filler improve the hot and cold shock resistance of the product and the toughness of the ceramic coating. The addition of borax and polyborosiloxane to the topcoat effectively improves the strength of the ceramic coating.
[0048] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A high-strength and high-toughness ceramic coating, characterized in that: The ceramic coating comprises a primer and a topcoat. The formula of the primer is as follows: by mass percentage, 20-30% nano-silica sol, 5-10% inorganic pigment, 5-10% modified inorganic filler, 30-40% methyl dimethoxy silane, 10-20% polyborosiloxane, 1-5% formic acid, and 5-10% deionized water; The preparation method of the modified inorganic filler is as follows: S1.1: Sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 20-30%, titanium diboride is dispersed in the sodium silicate solution, wherein the mass ratio of sodium silicate to titanium diboride is (1-2):1, and then 1wt% of a silane coupling agent is added, ultrasonicated for 4-6h to obtain a solid-liquid mixture, filtered and dried to obtain a mixture A; S1.2: Mixing mixture A and ceramic hollow microspheres in a mass ratio of 1:1 to obtain mixture B; S1.3: dissolving borax in deionized water to obtain a borax solution with a mass fraction of 30%, adding mixture B to the borax solution, wherein the mass ratio of mixture B to borax is 1:2, stirring in a stirrer at a speed of 200 r / min to obtain a solid-liquid mixture C; S1.4: Add 3 wt% urea to the solid-liquid mixture C, transfer to a muffle furnace preheated to 300°C, and burn for 1 to 3 minutes. After complete combustion, heat from the preheating temperature to 500 to 600°C, and calcine at 500 to 600°C for 2 hours to obtain a mixture D. After cooling to room temperature, crush and grind to obtain the modified inorganic filler; The formula of the topcoat is as follows: by mass percentage, 20-30% nano-silica sol, 5-10% hollow glass microbeads, 1-5% borax, 30-40% methyldimethoxysilane, 1-5% formic acid, 5-15% polyborosiloxane, and 10-20% deionized water.
2. A high-strength and high-toughness ceramic coating according to claim 1, characterized in that: The preparation method of the primer is as follows: S2.1: Put the inorganic pigment and the modified inorganic filler into a ball mill according to the proportion at room temperature and grind them at a speed of 800 r / min for 0.5-1 h to obtain a mixed powder; S2.2: Disperse the mixed powder in nano-silica sol, sonicate for 2-3 hours, and obtain primer component A after dispersion; S2.3: Mix formic acid and deionized water in proportion to obtain a primer C component, mix methyldimethoxysilane and polyborosiloxane in proportion, put into a mixer and stir at a speed of 300 r / min for 20 min to obtain a primer B component; S2.4: Add primer C component to primer B component to obtain primer B+C component, stir primer A component at a speed of 120-140 r / min, add primer B+C component after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth of 500 mesh or more to obtain the primer.
3. The high-strength and high-toughness ceramic coating according to claim 1, characterized in that: The preparation method of the topcoat is as follows: S3.1: Put hollow glass microspheres and borax into a ball mill according to proportion at room temperature and grind them at a speed of 600 r / min for 0.5-1 h to obtain a mixed powder; S3.2: Disperse the mixed powder in nano-silica sol in proportion at room temperature, perform ultrasonic treatment for 2-3 hours, and obtain topcoat component A after dispersion; S3.3: Formic acid and deionized water are mixed in proportion to obtain a topcoat component C, methyldimethoxysilane and polyborosiloxane are mixed in proportion, and the mixture is put into a mixer and stirred at a speed of 200 r / min for 10 to 20 min to obtain a topcoat component B; S3.4: Add the topcoat component C to the topcoat component B to obtain the topcoat component B+C, stir the topcoat component A at a speed of 120-140 r / min, add the topcoat component B+C after stirring for 0.5 h, and continue stirring at a speed of 120 r / min for 5 h, filter the stirred mixture using a filter cloth with a mesh size of 300 or more to obtain the topcoat.
4. The high-strength and high-toughness ceramic coating according to claim 1, characterized in that: The silane coupling agent in S1.1 is one or more of silane coupling agent KH-550, silane coupling agent KH-560, and silane coupling agent KH-792.
5. The high-strength and high-toughness ceramic coating according to claim 1, characterized in that: The particle size of the ceramic hollow microbeads in S1.2 is 3 μm.
6. The high-strength and high-toughness ceramic coating according to claim 1, characterized in that: In S1.4, the particle size of the modified inorganic filler is 800 mesh.
7. A method for using a high-strength and high-toughness ceramic coating, based on the high-strength and high-toughness ceramic coating according to any one of claims 1 to 6, characterized in that: The method of using the ceramic coating is as follows: S7.1: sandblast the surface of the substrate, and purge the magnesium alloy surface after sandblasting with nitrogen gas at a flow rate of 20 m / s, the purity of the nitrogen gas is 99.99%, and the purge time is 0.5 h; S7.2: First spray the primer on the treated substrate surface, with the spraying parameters of spraying distance 60 mm and spraying rate 80 mm / s; S7.3: Spray the topcoat directly after spraying the primer. The spraying parameters are spraying distance 40 mm, spraying rate 60 mm / s, and drying at 80℃ for 15 minutes after spraying. S7.4: Polish and grind the surface of the substrate after the topcoat has dried. First, use a grinding head composed of 500 mesh elastic modules to grind for 20 seconds, and then use a grinding head composed of 2000 mesh elastic modules to grind for 10 to 30 seconds. After grinding, bake and cure again to complete the use of the coating.
8. The method for using a high-strength and high-toughness ceramic coating according to claim 7, characterized in that: The material for sandblasting in S7.1 is brown corundum with a particle size of 200 mesh, the sandblasting distance is 50 mm, the sandblasting angle is 60°, and the sandblasting time is 10 min.
9. The method for using a high-strength and high-toughness ceramic coating according to claim 7, characterized in that: The pressure applied by the grinding head of the polishing hard grinding block in S7.4 to the tile surface is 1.5 MPa, and the pressure applied by the grinding head composed of the elastic module to the tile surface is 0.3~0.5 MPa.
10. The method for using a high-strength and high-toughness ceramic coating according to claim 7, characterized in that: The parameters for the baking and curing in S7.4 are first baking at 100° C. for 5 to 8 minutes at a low temperature, and then baking at 300° C. for 15 minutes.
Citation Information
Patent Citations
High-temperature-corrosion-resistant enamel coating and preparation method thereof
CN113149439A
Ceramic-based coating for enhancing corrosion resistance of boiler water-cooled wall and preparation method of ceramic-based coating
CN118185349A
Coating method of ceramic coating for relief etching pot
CN119346405A
Ceramic coating for gravure etching pot and coating method thereof
CN119410264A
Heat-resistant coating composition
JP1992239074A
Cited By
Modified fluorosilicone resin coating material with low thermal conductivity and high toughness as well as preparation method and application of modified fluorosilicone resin coating material
CN120888236A
Low-thermal-conductivity high-toughness modified fluorosilicon resin coating material, and preparation method and application thereof
CN120888236B